Clinical Characteristics and Outcomes of Pancreaticoduodenectomy (Whipple Procedure) in the Last Five Years at Prof. Dr. R. D. Kandou Hospital - Tendean, Michael; Tjandra, Ferdinand; Mambu, Toar; Ayawaila, Marven; Sihaloho, Eric (Universitas Sam Ratulangi, 2026)
Abstract: Pancreatoduodenectomy (Whipple) is the standard procedure for resectable pancreatic and periampullary neoplasms. Although techniques and postoperative care continue to evolve, this procedure is still associated with high morbidity and significant complications, such as pancreatic fistula and delayed gastric emptying. It is most commonly performed on elderly patients with pancreatic adenocarcinoma and requires ongoing evaluation to improve outcomes. A five-year review is necessary to assess trends, complications, and postoperative outcomes as a basis for improving the quality of surgical management. This was a retrospective descriptive analysis of adult patients who underwent pancreatoduodenectomy at Prof. Dr. R. D. Kandou Hospital between 2020 and 2025. The inclusion criteria were patients with complete medical records, including demographic data, surgical indications, surgical outcomes, and postoperative complications. Cases with incomplete data, surgeries performed outside the study period, or patients who died before postoperative evaluation were excluded. Univariate analysis was performed using SPSS version 30 to describe clinical characteristics and patient outcomes. Of the 35 patients, the distribution of gender and diagnosis (icteric vs. non-icteric obstruction) was relatively balanced. Most underwent a single Whipple procedure (65.7%) using the duct-to-mucosa anastomosis technique (80%). Postoperative complications occurred in 57.1% of patients, and 30-day mortality was 34.3%. The mean age of patients was 55.6 years, the duration of surgery was 370 minutes, the blood loss was 568 cc, and the length of hospital stay was 9.8 days. In conclusion, the Whipple procedure demonstrates variable outcomes with high morbidity and a 30-day mortality rate of 34.3%. End-to-side anastomosis is the most commonly used technique. Age, case complexity, and operative variability influence patient recovery and prognosis. Keywords: pancreatoduodenectomy; pancreatic neoplasm